2020
DOI: 10.3390/app10082764
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length as a Biomarker of Biological Aging in Shift Workers

Abstract: Shift work (SW) comprises a work schedule that involves recurring times of nonstandard work hours balanced to a fixed daily work plan with regular day work times and has been evaluated as “probably carcinogenic to humans” (Group 2A) by IARC. SW may result in increased age acceleration. This systematic review aims to elucidate the usefulness of telomere length as a biomarker of biological aging in shift workers. All studies analyzed underline a shortening of telomere length in SW, and aging in shift workers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 78 publications
(128 reference statements)
0
9
0
Order By: Relevance
“…There is evidence of accelerated telomere shortening in shift workers. In a recent systematic review of the literature, Ledda et al identified seven studies that underlined that the intensity of shift work is related to modest TL shortening [249]. For instance, a significant decrease in LTL was seen in nurses having worked in night shifts for ≥12 years (β = −0.07) [250], and salivary TL was shortest among those who worked >4 consecutive night shifts for ≥5 years [251].…”
Section: Shift Workmentioning
confidence: 99%
“…There is evidence of accelerated telomere shortening in shift workers. In a recent systematic review of the literature, Ledda et al identified seven studies that underlined that the intensity of shift work is related to modest TL shortening [249]. For instance, a significant decrease in LTL was seen in nurses having worked in night shifts for ≥12 years (β = −0.07) [250], and salivary TL was shortest among those who worked >4 consecutive night shifts for ≥5 years [251].…”
Section: Shift Workmentioning
confidence: 99%
“…Furthermore, obesity is an additional risk factor for injury, due to important physical limitations in movement and agility, which can reduce worker safety [ 11 , 12 ]. Metabolic syndrome is a clinical situation in which several interrelated factors contribute to increasing the possibility of developing diseases affecting the cardiovascular system and metabolism (e.g., diabetes) [ 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Souza et al demonstrated that occupational coal exposure was associated with shortened RTL [ 16 ], and a case-control study in India found that shorter RTL was associated with essential hypertension [ 23 ]. The telomere length of health care workers (mainly nurses) showed that shift work can lead to shortened telomere length, increased systemic inflammation, and oxidative stress imbalance [ 24 ]. The shift work of coal miners in this study may also be an important risk factor for telomere length, which deserves further research.…”
Section: Discussionmentioning
confidence: 99%